2004
DOI: 10.1126/science.1099859
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Vacuolar Protease, VPE, Mediates Virus-Induced Hypersensitive Cell Death

Abstract: Programmed cell death (PCD) in animals depends on caspase protease activity. Plants also exhibit PCD, for example as a response to pathogens, although a plant caspase remains elusive. Here we show that vacuolar processing enzyme (VPE) is a protease essential for a virus-induced hypersensitive response that involves PCD. VPE deficiency prevented virus-induced hypersensitive cell death in tobacco plants. VPE is structurally unrelated to caspases, although VPE has a caspase-1 activity. Thus, plants have evolved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
644
2
12

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(670 citation statements)
references
References 26 publications
12
644
2
12
Order By: Relevance
“…Caspase-1-like activities have been reported in several plant-microbe interactions. For example, vacuolar processing enzyme (VPE), a cysteine protease localized to the vacuole, is required for TMV-mediated HR-PCD and resistance (Hatsugai et al, 2004). Inoculation of tobacco with an incompatible strain of Pseudomonas syringae or B. cinerea triggered caspase-1-like activity that was suppressed in the VPE mutant background.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-1-like activities have been reported in several plant-microbe interactions. For example, vacuolar processing enzyme (VPE), a cysteine protease localized to the vacuole, is required for TMV-mediated HR-PCD and resistance (Hatsugai et al, 2004). Inoculation of tobacco with an incompatible strain of Pseudomonas syringae or B. cinerea triggered caspase-1-like activity that was suppressed in the VPE mutant background.…”
Section: Discussionmentioning
confidence: 99%
“…Other cell death routes are likely to be induced via NDR1 because AvrRpm1 triggered cell death was only suppressed to levels observed for ndr1, and we could not suppress NDR1-dependent cell death. These pathways could include vacuolar proteases or metacaspases (Hatsugai et al, 2004;He et al, 2008), but how these enzymes relate to autophagy is currently unknown.…”
Section: Multiple Routes To Cell Death In Plant Pathogen Interactionsmentioning
confidence: 99%
“…10,11 A paper in Science reported that VPE localizes in the vacuolar membrane and mediates virus-induced hypersensitive cell death by regulating the collapse of this membrane. 12 VPEs, including seed-type VPE and vegetative-type VPE, were originally discovered as cysteine proteinases responsible for the maturation of vacuolar proteins. 13,14 Elicitors can activate plant innate immunity.…”
Section: Role Of Vpe In Pcdmentioning
confidence: 99%
“…9 Therefore, the molecular identification of protein kinases with caspase activity will help us elucidate elicitor signal transduction. As VPE was identified to have YVADase activity and to be involved in various cell death responses, 12,19 we postulated that elicitor signals are transduced via VPEs in plants. …”
mentioning
confidence: 99%